Yes, you can rewrite \( 10^3 \cdot 5 \) using a single base raised to a power.
First, note that \( 10 = 2 \cdot 5 \). Therefore, we can express the \( 10^3 \) term in terms of its prime factors:
\[ 10^3 = (2 \cdot 5)^3 = 2^3 \cdot 5^3 \]
Now substitute this back into the original expression:
\[ 10^3 \cdot 5 = (2^3 \cdot 5^3) \cdot 5 = 2^3 \cdot 5^3 \cdot 5 = 2^3 \cdot 5^4 \]
To combine this into a single power of \( 10 \):
We know that:
\[ 10^n = 2^n \cdot 5^n \]
Now we need to express \( 2^3 \cdot 5^4 \):
This can be rewritten as:
\[ 2^3 \cdot 5^4 = 2^3 \cdot 5^3 \cdot 5 = 10^3 \cdot 5 \]
Since you cannot simplify \( 2^3 \cdot 5^4 \) any further into a single base of \( 10 \) without additional factors. Therefore:
The expression \( 10^3 \cdot 5 \) cannot simplify down into a single power of 10 without extra factors.
So the answer is No, you cannot write \( 10^3 \cdot 5 \) as a single power of 10 without additional factors.